One health manual: on handling zoonotic disease outbreaks in Malaysia: laboratory involvement - Mohamed, Ramlan; Amran, Fairuz; Awang Hamat, Rukman; Amin Nordin, Syafinaz; Adnan, Ariza; Md. Jinin, Zurin Azlin; Mohd Mohidin, Taznim Begam (Malaysia One Health University Network, 2017)
In recent times, several infectious and zoonotic diseases have emerged as major threats to the health of people and animals globally, resulting in suffering and death of human and animals. The One Health Manual, an initiative of Malaysia One Health University Network (MyOHUN), is the first local Manual to deal with zooneses outbreak investigation based on the One Health concept which is a multidisciplinary collaboration among a myriad of disciplines. This Manual will be a good resource for existing and future One Health workforce.